2008
DOI: 10.1007/978-1-60327-214-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Study Origin of Germ Cells and Formation of New Primary Follicles in Adult Human and Rat Ovaries

Abstract: The central thesis regarding the human ovaries is that, although primordial germ cells in embryonal ovaries are of extraovarian origin, those generated during the fetal period and in postnatal life are derived from the ovarian surface epithelium (OSE) bipotent cells. With the assistance of immune system-related cells, secondary germ cells and primitive granulosa cells originate from OSE stem cells in the fetal and adult human gonads. Fetal primary follicles are formed during the second trimester of intrauterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(167 citation statements)
references
References 37 publications
8
153
0
3
Order By: Relevance
“…Folliculogenesis in the adult ovary is characterized by extensive architectural remodeling that culminates in disruption of the coelomic epithelium and extrusion of the ovum at ovulation (1,2). After disruption, a series of molecular events initiates and executes repair of the epithelial wound (3,4).…”
mentioning
confidence: 99%
“…Folliculogenesis in the adult ovary is characterized by extensive architectural remodeling that culminates in disruption of the coelomic epithelium and extrusion of the ovum at ovulation (1,2). After disruption, a series of molecular events initiates and executes repair of the epithelial wound (3,4).…”
mentioning
confidence: 99%
“…In a later paper, the same group modified their view and suggested that bone marrow-derived germinal stem cells are distributed by peripheral blood to the mouse ovaries [203]. Another group provided evidence for the in vivo de novo differentiation of mesenchymal progenitor cells residing in the ovarian tunica albuginea into primitive granulosa and germ cells in the adult human female [204]. The same group also demonstrated the in vitro differentiation of cells derived from adult human ovarian surface epithelium into oocytes and granulosa cells [205].…”
Section: Formation Of Oocytes and Follicles In The Adult Femalementioning
confidence: 99%
“…This approach, possibly with the exception of transplant to the pelvic peritoneum, requires performing in vitro fertilization for fertility purposes. Nevertheless, there have been reports of spontaneous pregnancies after heterotopic transplantation to the subcutaneous and intramuscular tissues, possibly due to reintroduction of ovarian germinal cells with the tissue transplant [10,64]. Based on this hypothesis, germinal stem cells contained in the transplanted tissue would re-colonize the ovary/ies or would trigger the existing quiescent germinal stem cells to develop into follicles and oocytes capable of producing pregnancies.…”
Section: Ovarian Cortical Tissue Transplantmentioning
confidence: 99%
“…It has been a dogmatic belief that follicle reserve is established in utero in humans, and that there is no regeneration postnatally [9]. However, recent studies claimed 'regeneration' of new follicles from stem cells in adult human ovaries [10]. In support of this new notion is the observation that many women conceive years after experiencing premature menopause as a result of high-dose chemotherapy and or radiotherapy [11,12], or even after idiopathic primary ovarian insufficiency has been established [13].…”
Section: Introductionmentioning
confidence: 99%